PERHITUNGAN HARGA POKOK PRODUKSI, ACTIVITY BASED COSTING DAN SISTEM BIAYA KONVENSIONAL PADA PERUSAHAAN X. - Sova, Maya; Anwar, Juli (MAJALAH ILMIAH WIDYA, 2012)
The activity Based Costing (ABC) is a system to allocate all the cost that exist in production process based on the activitiesof the company so that it is more complicated than the traditional cost system. In the traditional cost system, all cost calculatedbased on the volume of activities so that the production cost unit can be higher or lower.The aim of this research is to know howto calculate the production cost by using ABC system (Activity Based Costing) or by Traditional Cost System. The method of writingis based on Field Research and library studies. The Collected data was analyzed descriptively. The result indicates that the calculationusing ABC System apparently can keep the main cost of production down in the amount of Rp 517.- for each unit of product